Trans Adolescence and their Decision about Identity and Sexual Life - Chinga Aspiazu, Yandri Vladimir (2023)
The gender identity and sexual rights are very complex issues, even in the world of law. International organizations such as the United Nations International Children’s Emergency Fund, the Inter-American Commission on Human Rights or the Inter-American Court of Human Rights have stated that the minors are subjects of rights related to sexuality and gender identity, because these rights are part of the free development of the personality. Thus, the objective of this research is to analyze, if in Ecuador the minorsare subjects to sexual rights and if they can freely express their gender identity. This research determined that the teenagers are subjects of sexual rights and gender identity, so that, the teenagers can exercise these rights but based on their faculties and capacities. For this reason, adolescents have the right to freely express and enjoy their sexuality; namely, they cannot suffer discrimination. Therefore, the State must guarantee transsexual adolescents dignified and equal treatment, the rectification of the registry of the new gender identity and a medical therapy that assures the person a harmony between the felt sex and the physical sex.